Interlending and document supply: a review of the recent literature; 93. Issue 4 (21st November 2016) - McGrath, Mike
Abstract : Purpose: This paper aims to review the current library and information science (LIS) literature for document supply, resource sharing and other issues such as open access (OA) that have an impact on the service. Design/methodology/approach: The approach is based on the scanning of about 150 journals, reports, websites and blogs. Findings: Of the 13 articles and reports reviewed, 12 are freely available, continuing the trend of increasing OA. As always, these days, much is happening on the OA front. Big Deals, demand-driven acquisition and discovery tools are reviewed. Originality/value: The only regular literature review that focuses on interlending, document supply and related issues.